The Automation of Invention. - Plotkin, Robert (Futurist)
The inventors of the future will write descriptions of the problems they want to solve and then give those descriptions to computers to figure out the solutions. This process can be called “inventing by wishing.” The problem description provided by the human is similar to a wish; the computer is like a genie that grants the wish by creating a design for a concrete product; and the result is the wish-come-true. The writer presents several examples of automated inventions.